Sexual and gender minority health: A roadmap for developing evidence-based medical school curricula - Giffin, Catherine; Glow, Sari; Lebo, Douglas Michael; Freeman, Tara; Miladinovic, Jovana; Hansen, Sonja; Brown, Chad; Karsenti, Nessika (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Background: Educating future physicians about sexual and gender minority (SGM) patients and their health care needs is an important way to mitigate discrimination and health disparities faced by this community. Canada, across its 17 medical schools, lacks a national standard for teaching this essential topic. This paper aims to review the best practices for teaching an SGM curriculum in undergraduate medical education and synthesize this information into actionable propositions for curriculum development.Methods: A scoping literature review was conducted to identify best practices for SGM teaching. The review elicited peer-reviewed and grey literature on best practices for SGM teaching, policy documents, and opinion pieces from medical education authorities and SGM advocacy groups. Through an iterative process with all authors, the Canadian Queer Medical Students Association (CQMSA), and the Association of Faculties of Medicine of Canada (AFMC), a set of propositions was developed.Results: The search yielded 1347 papers, of which 89 were kept for data extraction. The main outcomes of these papers were sorted along five repeating themes, which formed the basis for six propositions; two more propositions were then added after discussion with all authors.Conclusion: We present eight propositions for the development of a national standard for SGM education at the undergraduate medical level. These include standardizing learning objectives across all schools, using established curricular models to guide curriculum development, interweaving concepts across all levels of training, diversifying teaching modalities, providing faculty training, ensuring a safe space for SGM students and faculty, using OSCEs as a teaching tool, and involving the local SGM community in curriculum development and delivery.